Natural diet of three species of shrimp in a tropical coastal lagoon - Albertoni,Edélti Faria (2003)
The gut content of 495 specimens of Farfantepenaeus brasiliensis, 131 of F. paulensis (Penaeidae) and 102 of Macrobrachium acanthurus (Palaemonidae) were analyzed to establish the composition of their diets F. brasiliensis had as the most important feeding items in its diet larvae of Chironomidae, Polychaeta and Heleobia australis (Mollusca). For F. paulensis, the most important items were the same as for F. brasiliensis, but the order of importance of H. australis and Polychaeta was inverted. M. acanthurus had detritus as the most important item, followed by Chironomidae larvae, Odonata nymphs, and fragments of the macroalgae Chara. The results showed that the three species were omnivorous, with a varied diet including both components of macrofauna of benthos and associated to the macroalgae Chara and plant fragments and detritus.